Using innovative technology tools in organic chemistry education: bibliometric analysis - Pabuçcu-Akış Aybüke (Chemistry Teacher International, 2024)
This study focused on investigating the usage of popular innovative technology tools (augmented reality-AR, virtual reality-VR, artificial intelligence-AI, and 3D printing) in organic chemistry education. Although there is bibliometric analysis for the exploration of using innovative technology in educational context, there is further need for research focused on their usage in organic chemistry. Vosviewer and Biblioshiny software were used for bibliometric procedures. The Scopus database was selected to trace the articles published in journals. Following the eligibility process, the study was conducted with 30 articles for the time frame between January 2014 and June 2024. Performance analysis was utilized to reveal publications and citation trends with the top contributors. Bibliographic mapping was used to comprehend the conceptual, intellectual, and social structures of the retrieved data. The results revealed that articles on innovative technology tools have enormously increased in organic chemistry education recently. We found that the first innovative tool among the selected ones that is utilized in organic chemistry education is 3D printing while AI is the latest tool to start to be used in this scope. Although artificial intelligence seems to be the least studied tool among them, its popularity has recently seen an acceleration. VR and AR had the highest average citations per publication.